A Systematic Review on Commercially Available and Validated Sensor Technologies for Welfare Assessment of Dairy Cattle - Stygar, Anna H.; Gómez, Yaneth; Berteselli, Greta V.; Dalla Costa, Emanuela; Canali, Elisabetta; Niemi, Jarkko K.; Llonch, Pol; Pastell, Matti (Frontiers in Veterinary Science, 2021)
In order to base welfare assessment of dairy cattle on real-time measurement, integration of valid and reliable precision livestock farming (PLF) technologies is needed. The aim of this study was to provide a systematic overview of externally validated and commercially available PLF technologies which could be used for sensor-based welfare assessment in dairy cattle. Following PRISMA guidelines, a systematic literature review was conducted to identify externally validated sensor technologies. Out of 1,111 publications initially extracted from data bases only 42 studies describing 30 tools (including prototypes) met requirements for external validation. Moreover, through market search, 129 different retailed technologies with application for animal-based welfare assessment were identified. In total, only 18 currently retailed sensors have been externally validated (14%). The highest validation rate was found for systems based on accelerometers (30% of tools available on the market have validation records), while the lower rates were obtained for cameras (10%), load cells (8%), miscellaneous milk sensors (8%) and boluses (7%). Validated traits concerned animal activity, feeding and drinking behavior, physical condition and health of animals. Majority of tools was validated on adult cows. Non-active behavior (lying and standing) and rumination were the most often validated for the high performance. Regarding active behavior (e.g. walking), lower performance of tools was reported. Also, tools use for physical condition (e.g. body condition scoring) and health evaluation (e.g. mastitis detection) were classified in lower performance group. The precision and accuracy of feeding and drinking assessment varied depending on measured trait and used sensor. Regarding relevance for animal-based welfare assessment, several validated technologies had application for good health (e.g. milk quality sensors) and good feeding (e.g. load cells, accelerometers). Accelerometers-based systems have also practical relevance to assess good housing. However, currently available PLF technologies have low potential to assess appropriate behavior of dairy cows. To increase actors’ trust towards the PLF technology and prompt sensor-based welfare assessment, validation studies, especially in commercial herds, are needed. Future research should concentrate on developing and validating PLF technologies dedicated for assessment of appropriate behavior and tools dedicated for monitoring health and welfare in calves and heifers.